2019
DOI: 10.1038/s41435-019-0089-5
|View full text |Cite
|
Sign up to set email alerts
|

Transcribed B lymphocyte genes and multiple sclerosis risk genes are underrepresented in Epstein–Barr Virus hypomethylated regions

Abstract: Epstein-Barr Virus (EBV) infection appears to be necessary for the development of Multiple Sclerosis (MS), although the specific mechanisms are unknown. More than 200 single-nucleotide polymorphisms (SNPs) are known to be associated with the risk of developing MS. About a quarter of these are also highly associated with proximal gene expression in B cells infected with EBV (lymphoblastoid cell lines-LCLs). The DNA of LCLs is hypomethylated compared with both uninfected and activated B cells. Since methylation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…EBV infected B cell promoters tend to be hypomethylated ( 66 , 67 ), particularly at sites corresponding to B cell biological pathways, when compared to resting B cells ( 67 ). Furthermore, we previously found that MS risk SNPs that are eQTLs in LCLs (LCLeQTLs) are more likely to be methylated than by chance ( 68 ). It is therefore plausible that in the current study that differential methylation in the genders could underpin the response to estrogen signaling observed in serum-containing medium.…”
Section: Discussionmentioning
confidence: 99%
“…EBV infected B cell promoters tend to be hypomethylated ( 66 , 67 ), particularly at sites corresponding to B cell biological pathways, when compared to resting B cells ( 67 ). Furthermore, we previously found that MS risk SNPs that are eQTLs in LCLs (LCLeQTLs) are more likely to be methylated than by chance ( 68 ). It is therefore plausible that in the current study that differential methylation in the genders could underpin the response to estrogen signaling observed in serum-containing medium.…”
Section: Discussionmentioning
confidence: 99%
“… 80 Whilst there are also large epigenetic changes in response to EBV transformation of B cells to LCLs, with over two‐third of the genome exhibiting hypomethylation, 84 MS risk loci were in fact shown to be under‐represented in the hypomethylated regions. 85 It has been also reported that MS risk genes are highly over‐represented among host genes correlated with EBV DNA copy number level, whereas risk genes for diseases and traits not associated with EBV were only slightly or not over‐represented. 86 This study also showed that EBV DNA copy number is associated with 13% of MS risk loci in a genotype‐dependent manner.…”
Section: Interaction Between Ebv and Ms Genetic Risk Locimentioning
confidence: 98%
“…Despite the large transcriptomic changes that occur in a B cell upon infection with EBV and subsequent immortalisation, MS risk loci have been shown to be over‐represented in genes that are differentially expressed in LCLs compared with uninfected B cells 80 . Whilst there are also large epigenetic changes in response to EBV transformation of B cells to LCLs, with over two‐third of the genome exhibiting hypomethylation, 84 MS risk loci were in fact shown to be under‐represented in the hypomethylated regions 85 . It has been also reported that MS risk genes are highly over‐represented among host genes correlated with EBV DNA copy number level, whereas risk genes for diseases and traits not associated with EBV were only slightly or not over‐represented 86 .…”
Section: Interaction Between Ebv and Ms Genetic Risk Locimentioning
confidence: 99%
“…Tais fatores podem atuar juntos em nível epigenético, levando a alterações responsáveis pelo aumento da expressão de células inflamatórias 59,60 , bem como a diminuição de componentes regulatórios do sistema imune 61,62 .…”
Section: Ebv Vitamina D Tabagismo E Emunclassified